2016
DOI: 10.3892/mmr.2016.6052
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress influences the viability and morphology of human parametrial ligament fibroblasts

Abstract: Abstract. The present study aimed to investigate damage to human parametrial ligament fibroblasts by detecting cell proliferation, cytoskeletal structure, cellular alterations and senescence. Uterosacral and cardinal ligaments were obtained from 10 patients with cervical intraepithelial neoplasia grade II-III, who had received total vaginal hysterectomies, and fibroblasts were derived from this tissue. Fibroblasts were stretched using a four-point bending system with a force of 0 (control), 1,333 µ strain (1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…MTT assays also did not yield any significant effect of etoricoxib on cell viability, whereas the compressive force applied significantly reduced cell viability, that is, mitochondrial enzymatic activity, as assessed by the MTT assay. We thus hypothesize that either the mechanical stress itself [73] or an accompanying lack of oxygen [74] in our in vitro model, which is also supposed to occur during orthodontic tooth movement in vivo [75], most likely attenuated PDL fibroblast cell metabolism to a significant degree, whereas cell death was not significantly induced.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assays also did not yield any significant effect of etoricoxib on cell viability, whereas the compressive force applied significantly reduced cell viability, that is, mitochondrial enzymatic activity, as assessed by the MTT assay. We thus hypothesize that either the mechanical stress itself [73] or an accompanying lack of oxygen [74] in our in vitro model, which is also supposed to occur during orthodontic tooth movement in vivo [75], most likely attenuated PDL fibroblast cell metabolism to a significant degree, whereas cell death was not significantly induced.…”
Section: Discussionmentioning
confidence: 99%
“…Our group used the four‐point bending mechanics loading system to treat pelvic floor fibroblasts in the earlier studies. It was confirmed that the mechanical loading of suitable parameters could well simulate fibroblast stretch injury and cause cell damage 27–29 . Considering these research, we established a DRGs injury model in vitro that was stretched by a four‐point bending system in order to simulate pudendal nerve injury in the process of pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 92%
“…The previous study revealed that mechanical forces significantly effect cell activity, such as reduced cell proliferation, mitochondria vacuolization, or the cell cytoskeleton depolymerization. Among these mechanical forces, shear stress and hydrostatic pressure directly affect the physical and biological characteristics of cells and become important participants in cell viability [40,41]. In the final part of the simulation, we mimicked conditions such as hydrostatic pressure, capillary phenomenon, and liquid disturbance during spheroid formation.…”
Section: Discussionmentioning
confidence: 99%